The Effect Of Government Spending And Investment On Unemployment And Poverty Rate In North Penajam Paser District (PPU) East Kalimantan Province - Muhajir Muhajir; Aji Sofyan Effendi; Siti Amalia; Rahcmad Budi Suharto; Akbar Lufi Zulfikar (International Journal of Economics and Management Research, 2023)
Sources of financing are needed to manage and develop the region, which can come from Government Revenue and Investment in the area. This study analyzes the effect of Government Spending and Investment on the Unemployment Rate and Poverty Rate. Using secondary data and Structural Equation Modeling, empirically proven that greater Government Spending will decrease the Unemployment Rate and Poverty Rate. The perfect mediating role of the Un-employment Rate on the relationship between Government Spending and the Poverty Rate While Investment does not significantly affect the Unemployment Rate and Poverty Rate. Policies are needed so that existing investments, com-pulsory involving the local workforce, aim to reduce the area's poverty level.